The use of micro filter recovered palm oil mill effluent (pome) sludge as fish feed ingredient [LC5800-5808]. - Ahmed, Mahmud (2009)
This study examined the possible utilization of the retained lipid, protein, and carbohydrate from the palm oil mill effluent microfiltered using membrane pore size 0.45μm as fish feed ingredient for culture of Nile tilapia, Oreochromis niloticus.